Pengaruh Peran Guru Pak Untuk Meningkatkan Sikap Simpatik Kepada Peserta Didik Terhadap Karakter Kekristenan - Dorlan Naibaho; Ayu Allyssa Puteri Pasaribu (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
The important role of Christian Religious Education (PAK) teachers in developing students' Christian character. emphasizes the role of PAK teachers as correctors, facilitators, mentors, class managers, evaluators, and the importance of spiritual competence in education. Factors such as love, loyalty, justice and patience are the focus of forming Christian character. Factors such as love, loyalty, justice and patience are at the core of Christian character development. Apart from that, about the importance of Christian character education, the introduction of Christian ethical values and the formation of Christian mental character. The concept of character education includes values such as love, sincerity and balance in life, while the cultivation of ethical values includes integrity, sincerity and service leadership. Character formation in Christian mentality involves renewal of the mind, spiritual toughness, and healthy self-acceptance. Character formation in a Christian way of thinking includes renewal of the mind, mental flexibility, and healthy self-acceptance. Furthermore, developing emotional intelligence through Christian principles, including self-reflection, managing stress through prayer, forgiveness as a release of emotions, and building positive relationships. An emphasis on effective communication, peaceful management of conflict, and increasing hope and optimism is also an integral part of this approach. Thus, this journal article provides an illustration of how PAK teachers can play an important role in cultivating students' sympathetic attitudes towards Christian character, integrating Christian values and principles into character education, ethics and developing students' emotional intelligence.